Adsorption site-dependent transport of diclofenac in water saturated minerals and reference soils. (December 2019) - Yu, Chenglong; Bi, Erping
Abstract: Use of reclaimed water for irrigation is a main way for pharmaceutical compounds such as diclofenac getting into the soil environment. However, the role of minerals, especially iron oxides, in the diclofenac adsorption to soils with low soil organic matter (SOM) is still in the lack of evaluation. In this study, adsorption of diclofenac onto six minerals (five nature minerals-hematite, goethite, magnetite, kaolinite and aluminium oxide and one engineered mineral-activated aluminia) and five reference soils was investigated by column chromatography. Adsorption of diclofenac onto minerals and soils was totally reversible and interactions such as H-bonding were the primary mechanisms. Adsorption affinity of iron oxides was much higher than that of nature silicon and aluminum oxides. Diclofenac tended to be adsorbed by mineral surface -OH groups with high thermodynamic stability, which were dehydroxylated at high temperature. Compared with the SOM-dominated sorption of naphthalene, adsorption of diclofenac onto soils was controlled by bonding with surface -OH groups of iron oxides. Adsorption coefficients of diclofenac onto soils can be well predicted by contents of extracted Fe by diethylenetriamine pentaacetic acid (DTPA) instead of total iron oxides contents, suggesting that the bonding was adsorption site-dependent. These findings highlighted the importance of iron oxides in the adsorption of diclofenac (an anionic pharmaceutical compound) in soils with relatively low SOM (e.g., 1.03-3.45%). It also indicated that contents of effective surface -OH groups and DTPA-Fe were the promising parameters to develop the predictive models for diclofenac adsorption onto minerals and soils, respectively.